2015
DOI: 10.3109/1354750x.2015.1094142
|View full text |Cite
|
Sign up to set email alerts
|

Increased serum urea and creatinine levels correlate with decreased retinal nerve fibre layer thickness in diabetic retinopathy

Abstract: Correlation of increased levels of serum urea and creatinine with retinal nerve fibre layer (RNFL) thinning on spectral domain optical coherence tomography (SD-OCT) was studied in diabetic retinopathy (DR). Sixty consecutive cases and 20 healthy controls were included. Cases were divided into three groups: without DR, non-proliferative DR with macular oedema and proliferative DR with oedema. Serum urea and creatinine were measured using a standard protocol. Average (RNFL) was measured using SD-OCT. Increased s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
38
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 29 publications
3
38
0
Order By: Relevance
“…[28]The regulation of blood flow was considered in response to neuroactivity. However, recent research has pointed out that retinal neurodegeneration might precede microvascular dysfunction in DR. [29][30][31][32] Studies also have found out that RNFL thinning correlated positively with severity of DR. [33] In the present research, we also documented significant difference in average RNFL thickness in-between group comparison. RNFL thickness reduced as the severity of DR increased.…”
Section: Discussionsupporting
confidence: 75%
“…[28]The regulation of blood flow was considered in response to neuroactivity. However, recent research has pointed out that retinal neurodegeneration might precede microvascular dysfunction in DR. [29][30][31][32] Studies also have found out that RNFL thinning correlated positively with severity of DR. [33] In the present research, we also documented significant difference in average RNFL thickness in-between group comparison. RNFL thickness reduced as the severity of DR increased.…”
Section: Discussionsupporting
confidence: 75%
“…These Homocysteine is a sulfur-containing amino acid, and its high circulating levels are considered as a risk factor for many diseases including heart disease and diabetic complications [7,9]. Moderate increase in circulating homocysteine is considered to play a role in retinal abnormalities including endothelial cell dysfunction, ischemia, thinning of nerve fiber layers, neovascularization and blood-retinal barrier breakdown, the abnormalities intimately associated with diabetic retinopathy [40,41]. Our results show that the donors with established diabetic retinopathy have higher homocysteine levels in their retinal microvasculature, the site of retinal histopathology characteristic of diabetic retinopathy.…”
Section: Discussionmentioning
confidence: 99%
“…This finding suggests that there may be an association between renal function and retinal neuropathy. Srivastav et al 83 found an association between increased serum urea and creatinine levels and decreased RNFL thickness in patients with diabetes, while Shim et al 84 recently demonstrated that low eGFR levels are independently associated with POAG. However, there is a paucity of data regarding this potential association in the absence of diabetes.…”
Section: Discussionmentioning
confidence: 99%